A Review of Precast Concrete Pavement Technology - Ameen Syed (The Baltic Journal of Road and Bridge Engineering, 2020)
Precast concrete pavement (PCP) has proven itself to be one of the most efficient methods for repair and replacement of concrete pavement, as well as for construction of new pavement in the areas of heavy traffic. The application of PCP ensures fast construction of concrete pavement without compromising the quality of concrete. This paper provides a brief of various types of PCP that have been used worldwide and their application in the repair of damaged pavement, continuous construction of pavement, Airfield application and temporary pavement construction. It further discusses critical aspects of PCP that require careful analysis prior to its field implementation. The paper specially focuses on panel dimensioning, load transfer mechanism, lifting arrangement, stacking arrangement, transportation and base preparation for PCP. Suitability of different types of PCP for varying site conditions has been discussed. Innovative developments related to PCP and the future scope of this technology have also been discussed.